2005
DOI: 10.1128/mcb.25.1.422-431.2005
|View full text |Cite
|
Sign up to set email alerts
|

Growth Inhibition by the Tumor Suppressor p33ING1 in Immortalized and Primary Cells: Involvement of Two Silencing Domains and Effect of Ras

Abstract: ING1 was identified as an inhibitor of growth and has been described as a tumor suppressor. Furthermore, the expression of ING1 is induced in senescent cells and antisense ING1 extends the proliferative life span of primary human fibroblasts. Cooperation of p33ING1 with p53 has been suggested to be an important function of ING1 in cell cycle control. Intriguingly, it has been shown that p33ING1 is associated with histone acetylation as well as with histone deacetylation function. Here we show that p33ING1 is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
46
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 58 publications
5
46
0
3
Order By: Relevance
“…We have also observed that deletions including either the N-terminus or the Cterminus of p33ING1 are unable to trigger cell-cycle arrest to the same extent as the full-length protein, this effect being more obvious for the C-terminal construct. This is in agreement with previous observations in human diploid fibroblasts (Goeman et al, 2005). Interestingly, both deletion constructs showed an impaired capacity to increase p53 levels, and accordingly p21CIP1 and Mdm2 (Supplementary Figure 2).…”
supporting
confidence: 93%
See 4 more Smart Citations
“…We have also observed that deletions including either the N-terminus or the Cterminus of p33ING1 are unable to trigger cell-cycle arrest to the same extent as the full-length protein, this effect being more obvious for the C-terminal construct. This is in agreement with previous observations in human diploid fibroblasts (Goeman et al, 2005). Interestingly, both deletion constructs showed an impaired capacity to increase p53 levels, and accordingly p21CIP1 and Mdm2 (Supplementary Figure 2).…”
supporting
confidence: 93%
“…ING proteins have been linked functionally to the p53 pathway at different levels, including the control of p53 protein stability, as transcriptional cofactors, or through post-translational modifications of p53 (Nagashima et al, 2001;Nourani et al, 2001;Gozani et al, 2003). ING proteins also participate in chromatin remodelling through their association with histone deacetylases and histone acetyltransferases (Nourani et al, 2001;Feng et al, 2002;Kuzmichev et al, 2002;Vieyra et al, 2002;Xin et al, 2004;Goeman et al, 2005). The most extensively studied member of the ING family is p33ING1, one of the products of the ING1 locus (also referred to as p33ING1b, or ING1b elsewhere; Feng et al, 2002).…”
mentioning
confidence: 99%
See 3 more Smart Citations